Pengembangan Lembar Kerja Peserta Didik (LKPD) Dengan Menggunakan Model Pembelajaran Science, Technology, Engineering and Mathematics (STEM) Untuk Meningkatkan Efikasi Diri Pada Siswa Kelas XI Busana SMK Negeri 6 Padang - Khurnia Budi Utami (Fakultas Sastra Universitas Ekasakti, 2020)
This research begins with observations in schools that the learning process of mathematics has not fully achieved the learning objectives. Students 'interest in learning mathematics is still lacking and students' self-efficacy is still low. During the learning process, unsuitable teaching materials are used to solve these problems. From the existing problems, we need a new breakthrough that requires teachers to create appropriate teaching materials and be able to increase the self-efficacy of students. One of the breakthroughs referred to is by creating teaching materials in the form of Student Worksheets (LKPD) with the science, technology, engineering, and mathematics (STEM) learning model. This study aims to develop teaching materials in the form of LKPD using the STEM learning model to improve students' self-efficacy.This research is a development research that uses a 4-D development model which consists of 4 stages, namely 1) define, 2) design, 3) development (development) and 4) disseminate (deployment). LKPD developed and validated by several experts. Furthermore, it was tried out to see the practicality and effectiveness of LKPD in class XI Clothing 3 at SMKN 6 Padang. Practicality is seen through the results of the student and teacher response questionnaire analysis. Effectiveness is seen through the results of the final analysis of the student self-efficacy questionnaire.The results of the validation of LKPD by experts found that LKPD with the STEM learning model was categorized as valid. The results of using LKPD by teachers are obtained by practical LKPD, while the use of LKPD by students is obtained by LKPD which are very practical. The effectiveness of LKPD is seen from the results of the final analysis of the student self-efficacy questionnaire, the results of the study show that LKPD with STEM learning models can increase student self-efficacy. Thus, it can be concluded that the LKPD with the STEM learning model developed is valid, practical, and effective.